2019
DOI: 10.1016/j.jaip.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Prevalence Among Medicaid-Enrolled Children

Abstract: Background: Small-area asthma prevalence measures, which are crucial for targeting interventions, are currently sparsely available for children.Objective: This study aims to provide measures of in-contact asthma prevalence for the 2012 Medicaid child population, to highlight areas in need of targeted asthma interventions.Methods: Using the 2012 Medicaid Analytic eXtract (MAX) claims files, we develop two prevalence metrics differentiated by persistent or diagnosed asthma. We develop prevalence measures at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In the United States, the highest prevalence of asthma among Medicaid-enrolled children is within the southern Midwest region, which includes Texas. 5 Texas HSR 11 had the third highest proportion of pediatric beneficiaries with asthma care inpatient hospitalizations, outpatient hospitalizations, or physician visits in the Texas Medicaid program during 2014 (17.64%). 7 However, no asthma prevalence data have been reported for HSR 11 since 2013.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, the highest prevalence of asthma among Medicaid-enrolled children is within the southern Midwest region, which includes Texas. 5 Texas HSR 11 had the third highest proportion of pediatric beneficiaries with asthma care inpatient hospitalizations, outpatient hospitalizations, or physician visits in the Texas Medicaid program during 2014 (17.64%). 7 However, no asthma prevalence data have been reported for HSR 11 since 2013.…”
Section: Discussionmentioning
confidence: 99%
“…4 The state of Texas is one of the highest-ranking states for childhood asthma prevalence among Medicaid enrollees (12.97%). 5 As of 2020, Medicaid and the Children's Health Insurance Program (CHIP) provided health care benefits to 3,707,183 children in Texas. 6 The Texas Department of Health and Human Services reported that 7.00% of the children in Texas had a diagnosis of asthma during 2016.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resources include surveillance data from the CDC, 86 demographics data from the US Census Bureau, 87 and recent publications on asthma prevalence. 88 …”
Section: Prediction Of and Responding To Disease Spread During An Infmentioning
confidence: 99%
“…Resources include surveillance data from the CDC, 86 demographics data from the US Census Bureau, 87 and recent publications on asthma prevalence. 88 The effectiveness of interventions varies depending whether deployed for the general population, 4,50,89 high-risk populations, 3,21 children, or multiple age groups. 90 Timing and duration of interventions 91 and decision on the types (pharmaceutical, nonpharmaceutical, or combinations) of the responses 5,20,22,80,92 possibly affect the outcome of the preventive actions.…”
Section: Disease Spread Modelingmentioning
confidence: 99%